Dominós como recurso didático para o ensino de matemática - Oliveira, Oneide (2018)
This dissertation presents a possibility of the use of didactic materials in the teaching of Mathematics. In order to develop this work, dominoes were used as a pedagogical resource, seeking contributions as to their applicability so that a significant learning of the properties of addition and multiplication of natural numbers, certain algebraic properties, prominence for notable products, Girard relation and sums of arithmetic progressions, as well as in the use in Fibonacci sequences. The efficiency of the use of these materials was evidenced with the application of a teaching proposal regarding the properties of addition and multiplication of the natural numbers to the students of the 6th grade of Elementary School of the Escola Estadual de Ensino Médio São Izidro. After applying the teaching proposal, it was possible to verify that the dominoes, as a manipulative material, allowed for the variability of different examples and, therefore, a better understanding of what was being proposed, generating a significant increase of knowledge acquired in relation to properties studied.